FORMULASI DAN UJI STABILITAS SEDIAAN OBAT KUMUR DARI EKSTRAK ETANOL DAUN PANDAN WANGI (PANDANUSAMARYLLIFOLIUS ROXB) - Ira Pufaijah Ely; Lukman La Bassy (Jurnal Rumpun Ilmu Kesehatan, 2022)
Fragrant pandanus is a type of monocot plant from the pandanaceae family. Fragrant pandan leaves have various ingredients and can be used as antibacterial ingredients and are safe to use, which have been known empirically by the Indonesian people. There are many benefits to the fragrant pandan leaf plant (Pandanus amaryllifolius Roxb), namely as an analgesic (toothache medicine) and antibacterial. The purpose of this study was to determine the chemical content, formulation and stability test in mouthwash preparations. In this study, the maceration method is used which is used to filter simplicia containing chemical components that are easily soluble in liquid. The results of this study indicate that in the phytochemical screening test there are chemical compounds which include flavonoids, alkaloids, saponins, and tannins, which are thought to have contributed to bacterial activity. Research has also been carried out on the formulation and stability test of mouthwash preparations from the ethanol extract of pandan fragrant leaves (Pandanus amaryllifolius roxb) where the results show that the formulation can be used as mouthwash of fragrant pandan leaves (Pandanus amaryllifolius roxb) with different concentrations in formulation I. as much as 15.5%, in formulation II as much as 16.5%, and in formulation III 17.5%. And the physical quality test of the mouthwash includes an organoleptic test which has a distinctive smell of fragrant pandan leaves and menthol and the pH test has a stable pH of 5. The results obtained basically produce mouthwash with good physical quality.